The Implementation of Traffic Management Center (TMC) to Decrease Traffic Congestion: Case of Polres Kuningan Jurisdiction Area - Muzaffar Sondani, Irfan (Indonesian Journal of Police Studies, 2020)
The presence of TMC in Kuningan City Police Department is a policy made by the chief of Police Department to overcome various traffic problems. However, the existence of this policy is still unable to realize traffic safety and order in Kuningan City, especially in decreasing the traffic congestion during Eid celebrations. The increase of traffic congestion during Eid and holidays is a proof that traffic safety and order is not yet achieved in Kuningan City. These traffic congestion are caused by the increase of vehicle volume in Kuningan City. On the spots where the vehicle volume increased, the CCTV camera that supposed to connect to TMC was not connected. This research uses management, instruments, and elements of management theories, implementation theory, NTMC concept and traffic congestion concept. This research uses qualitative approach by adopting field research methods. The methods of data collection used were through interview, observation and document analysis. Qualitative data analysis in this research was done through data codification, presentation and conclusion. There are several findings in this resarch. First, TMC is not functional during ordinary days. Second, constraint on TMC is in the quantity of CCTV camera they possess. Third, TMC operators only rely on social media in their efforts to decrease traffic congestion. Fourth, the lack of monetary allocation in TMC can hinder the maintenance of inventory equipment. This research concludes that the main obstacle of Kuningan City Police Department’s TMC lies in the unavailablity of specific monetary allocation. The lack of this specific monetary allocation causes hindrance in the maintenance of TMC’s main equipment. The results of this research suggest that the chief of Kuningan City Police Department should single out a specific monetary allocation for their TMC to maintain the performance of TMC’s main equipment and to develop a better cooperation between the Traffic Unit of Kuningan City Police Department and the Department of Transportations and the Department of Communications and Informatics Key Words : TMC, Traffic Congestion, CCTV, Traffic Management Center.